If it's not what You are looking for type in the equation solver your own equation and let us solve it.
180=2x(5x-9)
We move all terms to the left:
180-(2x(5x-9))=0
We calculate terms in parentheses: -(2x(5x-9)), so:We get rid of parentheses
2x(5x-9)
We multiply parentheses
10x^2-18x
Back to the equation:
-(10x^2-18x)
-10x^2+18x+180=0
a = -10; b = 18; c = +180;
Δ = b2-4ac
Δ = 182-4·(-10)·180
Δ = 7524
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:x_{1}=\frac{-b-\sqrt{\Delta}}{2a}x_{2}=\frac{-b+\sqrt{\Delta}}{2a}
The end solution:
\sqrt{\Delta}=\sqrt{7524}=\sqrt{36*209}=\sqrt{36}*\sqrt{209}=6\sqrt{209}x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(18)-6\sqrt{209}}{2*-10}=\frac{-18-6\sqrt{209}}{-20}x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(18)+6\sqrt{209}}{2*-10}=\frac{-18+6\sqrt{209}}{-20}
| (x+2)^4=24 | | 0.6(1-6z)=-6 | | 32n+54=32 | | 0=-0,1x²+0,9x+1 | | (3x+8)4+6=6(2x+17) | | (2x+28)=(4x+5) | | 2(4-x)=3(3x-2) | | 3/x+2+3/x-2=2 | | 4(6r+3)+2(r+2)=4, | | 4r+12=4 | | (=10+5z)⋅2+5(z+4)= | | 6=2m-8 | | F(2)=3x^2+4x-4 | | 9w=57.78 | | 27+c=180+3 | | ×=1000.7x³+x²-10 | | 200+50=a+250 | | 0.7x³+x²-10x=100 | | x-27=100 | | 2x+12=57 | | (3-2X)+3(1-4X)-4(1-5X)=1(2-3x) | | h+78=141 | | 0.03x=250 | | 2=8x-4x-7x | | -9/10(x+8)=18 | | n+4=11.n | | F(x)=-7x^2+5x | | v/18=2/3 | | 2(3x+5)=50 | | j/13=16 | | .8(-2x-1)=24 | | 8c=11.2 |